Microstructural characterization of Friction stir assisted laminated lap welding of AA6063 sheets. (2022) - Singh Rajawat, Manvendra; Pagrut, Shravan; Dwivedi, Suryank; Omprakash,; Raj, Ratnesh; Rai Dixit, Amit
Abstract: Friction stir welding is a pioneering new technique for solid-state joining of Aluminium alloys, which also further strengthens the mechanical and microstructural properties of the base metal. Laminated lap welding on AA6063 sheets was performed using a stainless-steel tool with a square cross-section pin. The sample thus obtained was examined for their microstructural and hardness properties, and was characterized accordingly. Equiaxed grain structures are obtained commonly in friction stir welded samples. A refined grain size of ∼ 15 μm was observed in the microstructural characterization. The hardness profile depends on the degree of grain refinement as explained by the Hall-Petch effect. The microhardness was observed to be 135 % of the base metal hardness. The study has hinted towards the improvement of properties after friction stir lap welding and serves as a base for multilayer solid-state joining as a future prospect.